Aplikasi Sistem Informasi Kost Berbasis AndroidDi Universitas Muhammadiyah Surakarta - Setiawan, Rasyid Dani; , Fajar Suryawan, S.T., M.Eng.Sc, Ph.D (2017)
Universitas Muhammadiyah Surakarta is one of the best universities in solo. Many students from outside the city studiy at the Universitas Muhammadiyah Surakarta. Most of the new students are looking to find a place to live in solo. A mobile application can facilitate students to get an accommodation as desired. This application can run on Android and there are brief profiles of the accommodation, so that students can easily use it. This application also uses GPS technology to allow students easily see the location and the route to the acoommodation. These applications can benefit all parties, the students can search for accommodations as intebded and the owners can promote their place.